2017
DOI: 10.1021/acs.inorgchem.6b02249
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Intramolecular Electronic Communication in a Trinuclear Ruthenium Tropolonate Complex

Abstract: Dinuclear and trinuclear ruthenium complexes, [Ru(trop)(Ctrop)Ru(dppe)Cp] [2b; trop = tropolonato, Ctrop = ethynyltropolonato, dppe = 1,2-bis(diphenylphosphino)ethane] and [Ru(trop){(Ctrop)Ru(dppe)Cp}] (3), were synthesized, and their electronic and electrochemical properties were investigated in comparison with our previously reported complex [Ru(acac)(Ctrop)Ru(dppe)Cp] (2a). The electron-donating Ru(dppe)Cp unit and electron-accepting RuO unit are connected by Ctrop in these complexes. 2a incorporates acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Bimetallic or polymetallic inorganic and organometallic complexes bridged by π-conjugated spacers have received remarkable interest not only for their fascinating mixed valence chemistry but also for their emerging potential applications in molecular electronics, electrochromism, information storage, ion sensing, molecular magnetism, and dye sensitized solar cells . The pioneering discovery of Creutz–Taube ion, [(NH 3 ) 5 Ru-pyrazine-Ru­(NH 3 ) 5 ] 5+ , led the scientists to design and develop binuclear complexes to examine the extent of charge delocalization in their mixed-valence states and its fascinating spectroscopic properties .…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic or polymetallic inorganic and organometallic complexes bridged by π-conjugated spacers have received remarkable interest not only for their fascinating mixed valence chemistry but also for their emerging potential applications in molecular electronics, electrochromism, information storage, ion sensing, molecular magnetism, and dye sensitized solar cells . The pioneering discovery of Creutz–Taube ion, [(NH 3 ) 5 Ru-pyrazine-Ru­(NH 3 ) 5 ] 5+ , led the scientists to design and develop binuclear complexes to examine the extent of charge delocalization in their mixed-valence states and its fascinating spectroscopic properties .…”
Section: Introductionmentioning
confidence: 99%
“…In these complexes, the exchange of unpaired electrons or holes between the two metal termini occurs through the molecular bridging ligand, resulting in charge interconversion. A significant number of NIR absorbing mixed-valence metal complexes by varying the redox-active metallic termini and by modifying the π-conjugated spacer units linked between metal centers to modulate intramolecular electronic communication along the molecular backbone have been intensively investigated since the first synthesis of binuclear Ru 2 II,III complex [(NH 3 ) 5 Ru-pyrazine-Ru­(NH 3 ) 5 ] 5+ by Creutz and Taube. , In this regard, BODIPY-based π-conjugated congeners have emerged recently as excellent building units to construct NIR-absorbing organometallic mixed-valence species. Several research groups have reported long-range metal–metal coupling in ferrocenyl-functionalized BODIPYs or aza-BODIPYs, in which ferrocenyl moieties are connected directly to the macrocyclic core . Moreover, a conceptually reverse system bearing hybrid organic–inorganic redox-active centers has also been developed to investigate the electronic delocalization in this type of metal–organic electrophores. The electronic interplay between the organic electrophore and the metallic center often guides this type of dyad to NIR absorption.…”
Section: Introductionmentioning
confidence: 99%